Le Sezioni Unite della Cassazione e l’art. 11 del Trattato lateranense (Stato, Chiese e pluralismo confessionale, 2012)
SOMMARIO – 1. Una fattispecie semplice - 2. La nozione di enti centrali della Chiesa cattolica - 3. Il contenuto della garanzia pattizia - 4. La teoria dell’immunità ristretta nella giurisprudenza (caso Cermis) - 5. I limiti alla teoria dell’immunità ristretta (caso Calipari e caso Ferrini) - 6. La teoria dell’immunità ristretta e la sua applicazione agli enti centrali della Chiesa - 7. Immunità ristretta e limiti all’efficacia civile dei provvedimenti confessionali - 8. La portata attuale della garanzia pattizia - 9. (segue) La recente Convenzione monetaria tra lo Stato della Città del Vaticano e l’Unione Europea.Abstract : This essay examines the more recent judgements of the United Sections of the italian Court of Cassation on Article 11 of the Lateran Treaty, in the context of the vibrant juridical debate on this matter. It highlights how the United Sections of the Court defines this legal guarantee, granted by lateran Treaty to the central entities of the Catholic Church, in terms of “functional or restricted immunity” according to international law, so that - the Court adds - its basic foundation in the Italian constitution lies both in Article 7 (State-Church relations) and in Art. 10, concerning the automatic effect of the general international norms in the Italian system of law. Furthermore, the paper makes some relevant remarks about the main aspects and actual evolution of the doctrine of sovereign “immunity” through some recent judgements of italian law Courts. Then it underlines some emerging differences in its application - through Art. 11, Lat. Treaty - to the central entities of the Catholic Church, deriving from the special recognition of the “sovereignty of the Holy See in international matters” (Art. 2, Lat. Treaty). Finally it makes some concluding remarks about the actual meaning of this legal guarantee, taking the 2009 Monetary Agreement between the European Union and the Vatican City State into consideration too.